The impact of a training curriculum using balls suspended in the development of certain skills to football games air - Hussein, Raad (Journal of Physical Education, 2007)
The aim of research appears in making atraining course by using hanged balls. The aim is to develop some of air games skills in football to investment of better chances in scoring a number of goals in the match. The problem involves diagnosing the defeciency of some air games skills with first stage students. The experimental research has been applied on a sample consisting of (22) students devided into two equal groups. The researcher concludes that the training course with the use of hanged balls leads to develop all skills has been determined in the research. Also he recommends caring for training of these skills throuing the training course and football learning units for their importance in achieving and results in the match.